2023
DOI: 10.1002/saj2.20513
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of a large mid‐infrared soil spectral library between two Fourier‐transform infrared spectrometers

Abstract: Large and publicly available soil spectral libraries, such as the USDA National Soil Survey Center-Kellogg Soil Survey Laboratory (NSSC-KSSL) mid-infrared (MIR) spectral library, are enormously valuable resources enabling laboratories around the world to make rapid low-cost estimates of a number of soil properties. A limitation to widespread sharing of soil spectral data is the need to ensure that spectra collected on a secondary spectrometer are compatible with the spectra in the primary or reference library.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…2,016 of these soil samples were selected to represent the diversity of mineral soils found in the United States, and 90 samples were selected across Ghana, Kenya, and Nigeria. The 2,016 soil samples were obtained from USDA NRCS NSSC-KSSL Soil Archives and scanned by the Woodwell Climate Research Center and the University of Nebraska — Lincoln, which were made available with a CC-BY 4.0 license on Zenodo [32]. The number of unique samples correctly imported into the OSSL per original source and type of spectra is described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,016 of these soil samples were selected to represent the diversity of mineral soils found in the United States, and 90 samples were selected across Ghana, Kenya, and Nigeria. The 2,016 soil samples were obtained from USDA NRCS NSSC-KSSL Soil Archives and scanned by the Woodwell Climate Research Center and the University of Nebraska — Lincoln, which were made available with a CC-BY 4.0 license on Zenodo [32]. The number of unique samples correctly imported into the OSSL per original source and type of spectra is described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The same soil properties were evaluated using VisNIR, i.e., , , and . Lastly, the NIR Neospectra prediction models were tested with 90 soil samples from Ghana, Kenya, and Nigeria available through the public Neospectra database [32]. These samples were not used during model calibration but rather kept separated for external validation.…”
Section: Methodsmentioning
confidence: 99%
“…2) for proper evaluation of modeling results. Kennard-Stone deterministic sampling algorithm (Kennard and Stone, 1969) was run on SNV KSSL spectra to subset 50 samples, an optimal number for spectral standardization defined as per the previous analysis of Sanderman et al (2023). Before the subsetting, the KSSL SNV spectra were compressed by principal component analysis (PCA) to retain 99.99 % of the original variability.…”
Section: Instruments and Spectra Preprocessingmentioning
confidence: 99%
“…Spectral space transformation is a relatively new method and was first described by Du et al (2011). Its adoption in soil spectroscopy is very limited, although some recent studies have indicated that SST outperforms other spectral standardization methods, i.e., direct standardization (DS) and piecewise direct standardization (PDS), especially when a small number of standard samples are available to be shared across laboratories or instruments (Pittaki-Chrysodonta et al, 2021;Sanderman et al, 2023). The method is based on the transformation of spectra of a secondary instrument onto the spectral space of the primary one.…”
Section: Instruments and Spectra Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation